Epitaxial catalysts for oxygen evolution reaction: model systems and beyond. (25th July 2019) - Weber, Moritz L; Gunkel, Felix
Abstract: Epitaxy of complex perovskite oxides has arrived at atomic scale precision. This opens new chances and opportunities to the field of electrolysis and water splitting, where perovskite oxides show promising catalytic activity for the oxygen evolution reaction (OER). While representing ideal model systems for improving our scientific understanding of atomistic processes and scaling relations during OER, epitaxial heterostructures furthermore give access to atomic band engineering strategies and allow the generation of hybrid materials, which may combine beneficial properties of neighboring materials on the nanoscale. These strategies render novel opportunities to enhance chemical stability and to tune overpotentials of OER-active perovskite materials, not accessible in the bulk. Epitaxial catalysts can therefore play an important role in achieving new breakthroughs and guide lines in the field.